The Portrait of Scientific Approach Assisted by Video in EFL Reading: Participatory Action Research - Wahono, Suparwoto Sapto (TELL - US JOURNAL, 2023)
Learning English cannot be separated from reading skills. Explanatory text is one type of English text in reading skills. This text introduces students to natural events or phenomena that are often studied by students of natural science programs. The purpose of this study is to improve the students' ability to read explanatory texts with a scientific approach using video. This study used classroom action research with cycle stages consisting of planning, implementation, observation, and reflection. The data collection techniques used were observation with field notes, documents, and written tests. Findings suggest that the scientific approach using video improved the students' skills to read explanatory texts. It was proved that the average result of the pre-cycle was 70 and the average result of the first cycle was 75.